2002
DOI: 10.1053/rmed.2001.1237
|View full text |Cite
|
Sign up to set email alerts
|

Influence of deficient α1-anti-trypsin phenotypes on clinical characteristics and severity of asthma in adults

Abstract: Severe alpha1-anti-trypsin (AAT) deficiency implies a high risk of pulmonary emphysema development. The possible relationship between partial deficiencies of this enzyme and bronchial asthma remains controversial. The objective of this study was to ascertain the distribution of AAT phenotypes in a non-selected asthmatic patient population. Across-sectional study on a sample of 111 patients with asthma was carried out. Demographic and clinical variables were collected with serum IgE concentrations, plasma eosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
14
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 20 publications
5
14
1
2
Order By: Relevance
“…Aderele et al [18] reported that the serum levels of α 1 AT in asthmatic children were significantly lower in controls ( P < 0.02). We have observed a decreased α 1 AT activity in patients of asthma and these results are in agreement with other studies carried by various workers [9, 17, 18]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Aderele et al [18] reported that the serum levels of α 1 AT in asthmatic children were significantly lower in controls ( P < 0.02). We have observed a decreased α 1 AT activity in patients of asthma and these results are in agreement with other studies carried by various workers [9, 17, 18]. …”
Section: Discussionsupporting
confidence: 93%
“…The earlier studies correlating the asthma features and α 1 AT levels have shown variable observations. A study conducted by Miravitlles et al demonstrated that 22 out of 111 (19.8%) of asthmatics with a deficient phenotype of α 1 AT gene had normal values of α 1 AT [17]. Also, no significant differences were found when α 1 AT values were compared with each of the asthma patient groups classified according to severity criteria [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(29) Other studies, however, found no relationship between heterozygous phenotypes and clinical or functional changes in asthma patients. (30) There seem to be a relationship between occupational exposure to particulate inhalants and the development of pulmonary disease in patients with the PiZZ phenotype. (31) An association between AAT deficiency and cancer, including lung cancer, has also been suggested.…”
Section: Radiological Findingsmentioning
confidence: 99%
“…[21][22][23][24] However, patients with the PiZ allele, despite having lower values of the serum AAT than those with the wild type, this difference was not statistically significant, which might need a larger studied population to demonstrate a statistically significant difference. The AAT plasmatic concentration may vary in the patient's sample with other physiological or pathological states like age, asthma duration, an acute bronchial inflammation and/or the corticoid treatments.…”
mentioning
confidence: 99%